2022
DOI: 10.57174/jborn.v2i2.45
|View full text |Cite
|
Sign up to set email alerts
|

Ujı aktıvıtas sedıaan granul darı ekstrak etanol daun komba-komba (Chromolaena odorata L.) sebagaı larvasıda

Abstract: Komba-komba (Chromolaena odorata L.) merupakan salah satu tumbuhan yang dapat digunakan sebagai larvasida alami. Penelitian ini bertujuan untuk mengetahui aktivitas ekstrak daun komba-komba berbunga kuning dan bentuk sediaan granulnya sebagai larvasida. Daun komba-komba diekstraksi secara maserasi menggunakan etanol 96% kemudian didelipidasi menggunakan n-heksan. Ekstrak diidentifikasi metabolit sekundernya melalui skrining fitokimia secara kualitatif mengikuti metode Harborne. Pengujian aktivitas larvasida di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Phenolic compounds also inhibit Artemia salina larvae's taste receptors in the mouth, preventing the larvae from receiving a taste stimulus and preventing the larvae from recognizing their food. As a result, the larvae lack nutritional intake and die (Abriyani et al, 2022;Armadany et al, 2022;Cahya et al, 2022).…”
Section: Test For Acute Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Phenolic compounds also inhibit Artemia salina larvae's taste receptors in the mouth, preventing the larvae from receiving a taste stimulus and preventing the larvae from recognizing their food. As a result, the larvae lack nutritional intake and die (Abriyani et al, 2022;Armadany et al, 2022;Cahya et al, 2022).…”
Section: Test For Acute Toxicitymentioning
confidence: 99%
“…The resulting FTIR fingerprint spectrum contains a wealth of complicated data that can fully characterize a material's chemical properties (Purwakusumah et al, 2014). Earlier research on the toxicity test of the ethanol extract of komba-komba leaves revealed that the LC50 value of 225.81 ppm for komba-komba leaf extract (Chromoleana odorata L.) might result in up to 50% mortality of shrimp larvae (Armadany et al, 2022). The ethanol extract of komba-komba leaves (Chromolaena odorata L.) was tested for acute toxicity by Eriadi et al in 2016 on male white mice.…”
Section: Introductionmentioning
confidence: 99%